ЗАМОНАВИЙ ЭЛЕКТРОН ТАЪЛИМ РЕСУРСЛАРИНИ ЯРАТИШ БЎЙИЧА ТАВСИЯЛАР (Scientific journal of the Fergana State University, 2023)
The article discusses the use of AutoPlay Media Studio in creating e-learning resources, and also studies the technology of creating electronic resources. Based on the examples, recommendations for use in the education system are developed and provided